Equipamento para coleta e peneiramento de solo em profundidade variável - Bassini, Renato Tillmann (2020)
Current agriculture has the challenge of generating food for a growing world population, where there are several factors and challenges such as the development of new varieties, inputs and equipment in order to increase the supply of food. In order to verify the effectiveness of these new technologies, it is usually necessary to conduct experiments or perform laboratory analyzes using soil samples. If the soil sampling is carried out incorrectly, the results may not reflect the reality of the field, bringing erroneous final interpretations thus compromising all efforts employed in the development of these new products and or technologies. The objective of this work was to develop, build and evaluate equipment that allows the collection, preparation and storage of deformed soil samples in a semi-automated manner, up to a maximum depth of 20 cm. The prototype was developed and tested at the Federal University of Mato Grosso, Campus de Rondonópolis and region. For sample collections in layers smaller than 20 cm, the equipment generated losses of smaller diameter soil particles (silt and clay). In the 0-20 cm layer, the equipment provided collections similar to the manual procedure. For the soil classes with finer textures, mainly, there were no changes in the proportions of sand, silt and clay. The equipment allows the uniformity of the collection thickness in the layer of interest, reducing the intrinsic sampling error of the manual procedure. Having obtained the best productivity in the Red Latosol being possible to collect a total of approximately 9500 liters per hour and the lowest productivity was observed in the Argisol soil, where it is possible to collect a total of approximately 600 liters per hour, all in average values.